Attetion Deficit Hyperactvity Disorder (ADHD) Pada Anak Berkebutuhan Khusus Di Sekolah Inklusi - Nurfadhillah, Septy; Magdalena, Ina; Wulandari, Amalia Sri; Noviantik, Dicha; Sabil, Fadel; Tri setyani, Gading Retna; Rabani, Muhamad Ariq Fakhri; Azizah, Nur; Novitasari, Novitasari; Rossy, Rossy; Jannah, Raudhatul; Rojana, Salsa; Ramadhan, Yusuf Fadillah (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out about Attention Deficit Hyperactivity Disorder (ADHD) at SDIT LAA TAHZAN CITRA, Tangerang City. The research procedure used is a qualitative procedure with descriptive presentation of the information. This information gathering method uses interviews, observation and documentation. Sources for collecting this information were obtained from sources/informants as well as from research sites. The results of this research were quite well carried out and neatly arranged. This research uses interview methods and observations of one of the teachers at SDIT LAA TAHZAN CITRA. This interview was attempted directly/offline by visiting the source..